Abnormal uterine bleeding as first symptom of acute promyelocytic leukaemia: a case report and literature review - Okafor, Love Chimezirim; Obi, Ebelechukwu Adaobi; Ukoha, Chinenye; Meraiyebu, Aminyene Essien; Iseko, Kingsley Iyoko; Olua, Uchechi Nzerem (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Abnormal uterine bleeding is common within gynaecology practice. It affects up to one-third of women during their lifetime. Hematological cancer is a rare form of coagulopathy leading to abnormal uterine bleeding. Uterine bleeding caused by coagulopathy as a complication of acute promyelocytic leukaemia can be fatal. The aim was to document a rare case of acute severe abnormal uterine bleeding as first symptom of haematological cancer (Acute Promyelocytic Leukaemia). She was a 45-year-old Para 2 woman who presented at the emergency room with chief complaint of uterine bleeding of six days duration. She also developed a throbbing headache that suddenly intensified, initially on the left side of her head, radiating to the periorbital area. Assessment of Acute promyelocytic Leukaemia complicated by Subarachnoid haemorrhage was made. She was referred to National Hospital Abuja for further management. Uterine bleeding caused by coagulopathy as a complication of acute promyelocytic leukaemia can be life threatening, hence early diagnosis and treatment is imperative.